Perceptions of smoking on public health practice, factors affecting and the campaign of government : A case study in Universiti Utara Malaysia, Sintok - Asyraf, Azizan (2015)
This review is about the perception of the impact of smoking on public health, the factors that influence and campaigns carried out by the government involving 368 respondents from Universiti Utara Malaysia, Sintok. The instrument used was a set of questionnaire consisting of four section, section A relevant background of the respondents, section B requires the respondent to answer yes, no or do not know to public health, section C, which requires the respondent to answer the questions based on Likert Scale Strongly Disagree (SD), Disagree (D), Not Sure (NS), Agree (A) and Strongly Agree (SA) and section D related to the government's campaign. Data and feedback are processed and analysed quantitatively using SPSS (Statistical Package for Social Sciences) version 21 for frequency, percentage and mean. The study found that peer pressure is a strong factor in influencing more than a factor of smoking parents. The study also found that respondents have knowledge about the effects of smoking on the health angle. As the proposal for further study will focus on its own internal factors that encourage them to smoke more deeply